2019
DOI: 10.1111/1467-8489.12316
|View full text |Cite
|
Sign up to set email alerts
|

Hedonic pricing and the role of stud fees in the market for thoroughbred yearlings in Australia

Abstract: Using data from one of Australia's largest thoroughbred auction houses, we investigate the price determinants of thoroughbred yearlings sold at auction. We include novel key variables to construct hedonic pricing models and examine the relative role of stud fees compared to the wide range of attributes in the pricing of yearlings. We find that the price effect of stud fees is influenced by the value buyers place on both the characteristics of sires and the characteristics of sire side siblings. The findings im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…In accordance with most previous studies, 7 , 8 , 9 , 11 , 20 , 21 colts were demonstrated to commanded significantly higher sales prices than fillies. Additionally, investigations of confounding revealed that sex was also associated with catalogue placement.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In accordance with most previous studies, 7 , 8 , 9 , 11 , 20 , 21 colts were demonstrated to commanded significantly higher sales prices than fillies. Additionally, investigations of confounding revealed that sex was also associated with catalogue placement.…”
Section: Discussionsupporting
confidence: 91%
“…In keeping with this, the only other study to evaluate yearling sales in the UK also demonstrated that if both dam and progeny had raced and won, then the progeny's race performance had a significantly greater influence on sales price than that of the dam 11 . Progeny race performance attributes have consistently been positively associated with yearling sales price in previous studies 6,7,11,18–20,23 . The present study, however, provides additional novel detail on this established relationship, with modelling of interactions demonstrating that the effect of SRW is significant only in yearlings from cheaper sires.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, the use of maternal siblings does have the benefit of comparing to horses of similar bloodlines, which the Control Group B in this study was lacking. Although yearling sales prices have been shown to be related to a sire's stud fee and progeny ( 30 ), the effect of sire was not adjusted for in this study because firstly osteochondrosis has a genetic component, and secondly to avoid problems in the analysis and interpretation since there were numerous sires which had only one or low numbers of offspring.…”
Section: Discussionmentioning
confidence: 99%